PKP-006 Comparison between the use of total/ideal/adjusted body weight for empirical vancomycin dosing in obese patients. (24th March 2015) - Mensa, M; Manzaneque, A; Soy, D; Codina, C
Abstract : Background: Pharmacokinetic studies have suggested that total body weight (TBW) could be the optimal approach to calculate the dose of intravenous vancomycin (15–20 mg/kg TBW every 8–12 h) for target achievement (Css > 15 mg/L). 1 However, recent data concluded that the use of adjusted body weight (ABW) might be a better approach in obese patients. 2 Purpose: To determine which is the preferred method (TBW, ideal body weight (IBW) or ABW) to optimise vancomycin treatment in obese patients. Material and methods: Retrospective, non-interventional, observational study. Inclusion criteria: >18 years-old, body-mass-index (BMI) ≥30 kg/m 2, creatinine clearance ≥60 mL/min, and vancomycin TDM at steady-state. Non-obese patients were included as a control group. Patients were identified by reviewing TDM reports. Vancomycin theoretical total daily doses (15–20 mg/kg) were calculated using TBW, IBW and ABW for each patient. They were compared with the dose used in our patients after TDM (Bayesian forecasting; PKSAbbot Software; target: Css > 15 mg/L) (TDM dose). Dose differences greater than 10–12.5% of the TDM dose were considered unsuitable, since they could be related to clinical failure. Wilcoxon's test analysis was performed using SPSS; (p < 0.05). Results: Forty obese patients: 35% men; 60.4 ± 12.6 years-old; BMI: 33.3 ± 2.7 kg/m 2 . Compared to the TDM dose and considering 15–20 mg/kg: (i) Overdosage was observed in 72.5 (95%), 25 (47.5%) and 32.5 (72.5%) patients for TBW, IBW and ABW, respectively. Statistically significant differences were seen, with mean dose differences higher than 500 mg in the 20 mg/kg group. (ii) Underdosage was seen in: 22.5 (5.0%), 75 (45%) and 67.5 (27.5%) respectively. Statistically significant differences were seen with mean dose differences lower than 400 mg in the 15 mg/kg group. No relevant differences were observed in the control group. Conclusion: Compared to the TDM dose, a high incidence of overdosage would be observed by using TBW. In our obese patient cohort, ABW might be the best approach to set the dose of intravenous vancomycin (15–20 mg/kg), as already seen in previous literature. 2 References: Rybak M, Lomaestro B, Rotschafer JC, et al . Therapeutic monitoring of vancomycin in adult patients: a consensus review of the American Society of Health-System Pharmacists, the Infectious Diseases Society of America, and the Society of Infectious Diseases Pharmacists. Am J Health Syst Pharm 2009;66:82–98 Leong JV, Boro MS, Winter M, et al . Determining vancomycin clearance in an overweight and obese population. Am J Health Syst Pharm 2011;68:599–603 No conflict of interest.